The impact of human resources technology on organisational effectiveness in South Africa - Mahlulo, Bongisa (My University, 2020)
The purpose of this study is to investigate the perceived influence of the advanced HR technology on organisational effectiveness in South African companies. This advanced technology is used globally, and the implementation is localised to meet South African legislative requirements. The study covers the impact of disruptive technology in human resources (HR) and how it influences organisational effectiveness. The increasing digitalisation of functions is transforming how the human resources department provides a service to internal customers. There are rapid changes in managing HR processes due to advances in technology. Organisations implement human resources technology to automate and enable HR processes such as recruiting, onboarding, performance management, learning, compensation, remuneration, succession and development. The alignment between people, process and technology is a crucial part of the implementation. There is an expectation that this alignment should have an impact on organisational effectiveness. The purpose of implementing HR technology is to improve the efficiency of the HR department, streamline HR processes in relation to the HR operating model and strengthen HR as a strategic partner to achieve organisational success. The growing literature on the introduction of HR technology has explored a range of broad goals of efficiency, strategic orientation, service delivery and standardisation. The study explores the influence of adopting latest modern technology on organisational effectiveness. The study was conducted with two organisations that have adopted modern technology. Structured interviews, case comparison of the intended goals for implementing HR technology, perceived outcomes and influence on organisational effectiveness of these companies was analysed. In conclusion, evidence from both literature and the data collected from interviews confirm that defining strategic objectives is the foundation to identify business initiatives and provides a clear criterion on measuring organisational effectiveness. Furthermore, there is a limitation in providing quantitative evidence of the direct impact of implementing HR technology on organisational effectiveness due to the fact that the measurement of the outcomes is performed in isolation of other business functions, i.e., not in a holistic manner to include finance, procurement, sales & operations, and research & development initiatives. This study went further to discover that modern technology has an impact on employee data, engagement and experience, not only transaction-based HR services. In return, employee data provides the ability to produce predictive analytics that help to support the strategic business objectives.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Innovation Studies to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Adoption; Disruptive technology; Digitalisation; Human resources technology; Organisational effectiveness; SDG-8: Decent work and economic growth